Place, space and time: contextualizing workplace subjectivities - Halford, Susan; Leonard, Pauline (2006)
This paper explores the relations between management discourse and employee subjectivity in the process of organizational change, drawing on a new empirical study of doctors and nurses working in the British National Health Service (NHS). It builds on recent critiques of more muscular accounts of discourse to examine the manoeuvres made by working subjects in response to managerialist discourses of the entrepreneurial self. While others have shown the alternative discourses including gender, age and profession are important here, this paper argues that we must pay attention to the spatial and temporal contexts within which such generic discourses are received and understood in order to interpret the practices of subjectivity and power in organizational life. We suggest that this approach allows new insights to policy concerns in the NHS; to our understanding of the nature of work subjectivities; and to sociological understandings of organizational power. - Reproduced.
Keywords: Organizational change